(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
Among the academic subjects, Ancient Studies are those considered the most conservative. However, through interdisciplinarity (particularly through the dialogue with Archaeology), this field of study has managed to reach more critical perspectives, mainly in researches on love and sexuality. This work keeps a dialogue with the research carried out by the classicist Pedro Paulo Funari, who, in turn, has inspired many Brazilian researchers to break up the normative models, questioning old concepts and patriarchal values to give rise to a more libertarian classical antiquity. After presenting a discussion on gender and sexuality in Ancient Rome, a theoretical debate is proposed. Later on, some paintings of erotic relationships, showing diversified practices (particularly emphasizing homoerotic relationships), found in a suburban bath in the Archaeological Site of Pompeii, are presented to evince how differently individuals interpellated norms, to question the definition of pornography and to deal with the relationships between the images and their contexts.